Roy Honeycutt, Rodeo Stock Contractor, Alamosa, TX
The Amon Carter Museum in Fort Worth, Texas, and its director Mitchell A. Wilder, had built a unique collection of nineteenth and twentieth century photographs on the west. Wilder saw a portrait of ilbur powell, a ranch foreman, which was one of a series Richard Avedon had taken on July 4, 1978, in Ennis Montana. He proposed that Avedon continue his work with the sponsorship of the museum. wilder and Avedon agreed that the exhibition would be completed in five summers and would open at the Amon Museum in the Fall of 1985 and that the negatives would become part of the museum's archives. Wilder died in April 1979 but support of the project continued through the museum, the collection and exhibition was titled, "In The American West."